Monomeric M2e antigen in VesiVax® liposomes stimulates protection against type a strains of influenza comparable to liposomes with multimeric forms of M2e. (3rd July 2017) - Adler-Moore, J. P.; Ernst, W.; Kim, H.; Ward, N.; Chiang, S. M.; Do, T.; Fujii, G.
Abstract: Given the interest in the ectodomain of the matrix 2 (M2e) channel protein as a target for development of a universal influenza vaccine, we examined the role of the antigen configuration of M2e in generating a protective immune response. A series of M2e mutations and a truncated M2e segment were prepared as a means of controlling the formation of monomer, dimer, and higher order multimeric forms of M2e. Each of these M2e peptides was incorporated into a liposome-based vaccine technology platform previously shown to stimulate a protective response to influenza A infection using M2e as a mixture of monomers, dimers and multimers (L-M2e1-HD/MPL). Our results using these modified forms of M2e produced 90–100% survival following lethal challenge with H1N1 (A/PR/8/34) in both inbred BALB/c and outbred Swiss Webster mice vaccinated with a truncated monomeric form of the M2 protein, M2e1–15 in liposomes. These observations show that a tetrameric configuration is not required to elicit significant protection when the M2e antigen is formulated in immunogenic liposomes and further, that the first 15 amino acids of M2e likely play a primary role in providing the protective immune response.